2007
DOI: 10.19027/jai.5.167-177
|View full text |Cite
|
Sign up to set email alerts
|

Inventarisation of Parasite in ”Dumbo” Catfish Clarias sp. from Bogor Region

Abstract: <p>Outbreak of parasites can reduce aquaculture productivity or even cause mass mortality of fish. Few quantities of parasite infection may still be tolerated by the host, however high intensity of infection can impair to fish metabolism or even damage of organelle.  Proper treatment can be done when parasite infecting fish is known.  This study was conducted to record parasite infecting "dumbo" catfish <em>Clarias</em> sp. that is reared by farmers in three location at Bogor, i.e. Cimanggu, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 1 publication
1
4
0
8
Order By: Relevance
“…The prevalence and intensity value of ectoparasites value in Aceh Besar District were higher compared to several other farming areas in Indonesia, such as in Gresik (Lestari, 2011) and Deli Serdang (Daulae et al, 2018). Number and types of ectoparasites that infect catfish in Aceh Besar aquaculture ponds were similar to the number and types of ectoparasites that infect catfish in Deli Serdang farming areas (Daulae et al, 2018), however, the number and types were less than those found to infect catfish in Bogor (10 types) (Hadiroseyani et al, 2006). This thought influenced by the water condition of the cultivation pond, which was relatively unpolluted and the lacking of anthropogenic activities around the farming areas.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The prevalence and intensity value of ectoparasites value in Aceh Besar District were higher compared to several other farming areas in Indonesia, such as in Gresik (Lestari, 2011) and Deli Serdang (Daulae et al, 2018). Number and types of ectoparasites that infect catfish in Aceh Besar aquaculture ponds were similar to the number and types of ectoparasites that infect catfish in Deli Serdang farming areas (Daulae et al, 2018), however, the number and types were less than those found to infect catfish in Bogor (10 types) (Hadiroseyani et al, 2006). This thought influenced by the water condition of the cultivation pond, which was relatively unpolluted and the lacking of anthropogenic activities around the farming areas.…”
Section: Resultssupporting
confidence: 54%
“…and Ichthyopthyrius multifiliis (Figure 2). Several previous studies have reported that these ectoparasites also infect catfish in many places in Indonesia, for instance Semarang (Hasyimia et al, 2016), Bogor (Hadiroseyani et al, 2006) and Makassar (Anshary, 2008). Besides infecting catfish, these ectoparasites also have been reported to infect several species of fish such as goldfish (Carriasus auratus) (Anshary, 2008), carps (Cyprinus carpio) (Irwandi et al, 2005), tilapia (Oreochromis niloticus) (Mulia, 2010), panga (Pangasius hypophthalmus) (Islami, 2017) and milkfish (Chanos chanos) (Riko et al, 2012).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Gyrodactylus sp. pada ikan lele sering ditemukan seperti di kolam budidaya tradisonal dan kolam bioflok di Aceh Besar [26], menginfeksi lele dumbo di kabupaten Bogor [27], lele sangkuriang di Kendal [28] dan menginfeksi ikan lele dan nila di Kota Kupang [14], [15]. Prevelensi dan intensitas keberadaan parasit dapat berbeda disuatu tempat seperti Dactylogirus sp.…”
Section: Intensitasunclassified
“…yang ditemukan memiliki ciri-ciri tubuh, yaitu tubuhnya pipih memanjang, memiliki empat tonjolan dan dua bintik mata pada bagian anterior, memiliki sucker (alat penghisap), memiliki Ophisthaptor terdapat dibagian posterior dengan sepasang kait (anchors), bagian ophisthaptor terdapat 14 kait marginal hook yang melingkari bagian tepi ophisthaptor yang berfungsi untuk melekatkan pada insang ikan. Hal ini sesuai dengan pernyataanHadiroseyani et al (2006), bahwa ektoparasit Dactylogyrus sp. pada bagian anterior terdapat bintik mata dan empat tonjolan dan bagian ophisthaptor terdapat 14 kait marginal hook pada tubuhnya.Hasil penelitian yang telah dilakukan, Dactylogyrus sp.…”
unclassified